Borde como articulador de ciudad (2017)
With the arrival of the Metro to Bogotá, the architects asked some questions regarding the city and the consequences of the arrival of this mass transit medium, my first concern regarding the arrival of the elevated metro and more about the second stage that will be built on Avenida Caracas, is the lack of connection that are presented between the eastern and western side of Avenida Caracas as a historical process, the eastern side of Caracas has more construction and investment than the western side only need to take a tour of this important avenue to see the situation, so my challenge from the beginning was to generate a building that managed to integrate and improve the connection as well as hosting the last Metro station. The project is constituted of two metropolitan equipments with a central connection, the subway station, the place of intervention is the Avenue Caracas between streets 74 and 75. And it aims to generate a building for the city, which connects the metropolitan part of the Metro and the barrial part of San Felipe and Chapinero. The project is based on the mat building, in addition to the vernacular architecture, Jane Jacobs City concepts, the architecture seen as a system of Japanese metabolism, Louis Kahn, among others. All these concepts come together to make way for a building that behaves like a system that makes part of the city more than an isolated building. This system of construction aims to be flexible, replicable and versatile according to the needs of the users and the place, it is a system that can be replicated in all the stations of the metro and can adapt to the different conditions of Bogotá.--Tomado del Formato de Documento de Grado..